Study of tunneling and oscillation in a GaAs/〖Al〗_(0.3) 〖Ga〗_(0.7) As superlattice: using transfer matrix method - Shrestha, S; Bhusal, N; Byahut, S.; Sarkar, C. K. (BIBECHANA, 2021)
The study of the superlattice (SL) system in lower dimensions, which shows tunneling and oscillation of particles, is very interesting from the point of view of fundamental physics and is important for devices. Here, we present the results of our calculations related to tunneling/oscillations in a general SL system using a Symmetrical Quadruple Well (SQW) potential. This class of problems is handled using a transfer matrix (T-matrix), which is obtained by taking the solution of the Schroedinger equation with appropriate boundary conditions on either side of SQW and then repeatedly applying it for the SL system. The electron wave functions in the system are found to be either in a symmetric or an anti-symmetric state with a very small energy difference between the two, leading to oscillations between these states. In this study, probability density and period of oscillation of the particle in SQW is calculated. The result is useful for high-frequency operations in devices using SL.BIBECHANA 18 (1) (2021) 91-99